Analisis Efektivitas Strategi Pemasaran Digital pada UMKM Kuliner : Studi Kasus: UMKM di Pasar Raya MMTC Medan (Lembaga Pengembangan Kinerja Dosen, 2026)
The purpose of this study is to analyze and evaluate the effectiveness of digital marketing strategies implemented by Micro, Small, and Medium Enterprises (MSMEs), particularly those engaged in the culinary sector, within the Pasar Raya MMTC (Medan Metropolitan Trade Center) area in facing digital era competition. The research method employed is descriptive qualitative with a case study approach. Data collection involved in-depth interviews with MSME owners, observation of digital promotional activities (Social Media and Marketplaces), and content analysis. The results indicate that the most effective and commonly used digital strategies include: (1) Marketplace Optimization (focusing on discount and flash sale features), (2) Social Media Marketing Utilization (Instagram and TikTok for visual/video content), and (3) Collaboration with Local Micro-Influencers or food vloggers. The effectiveness of these strategies is measured by the increase in sales volume (an average of 20-30% after digital adoption) and improved brand visibility. The main obstacles encountered by MMTC MSMEs are the lack of consistency in content creation, limited funds for paid advertising, and insufficient understanding of digital data analytics. This study concludes that digital adaptation is essential, but it must be supported by improving digital literacy and providing targeted assistance focused on analyzing the return on investment (ROI) of digital marketing activities for sustainable growth.